Interação de biomarcadores de neuroimagem na Doença de Alzheimer : β-amiloide, substância branca e metabolismo cerebral - Schilling, Lucas Porcello (2016)
The pathophysiology of Alzheimer’s disease (AD) involves several pathological mechanisms, including amyloid-β and neurofibrillary tangles deposition, white matter changes and neurodegeneration. In this tranversal study, we investigated the interaction between white matter (WM) integrity and amyloid-β deposition as a potential determinant of cerebral hypometabolism in the Alzheimer’s disease (AD) continuum. Using the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, ninety-six subjects (cognitively normal (CN), n = 27; mild cognitive impairment (MCI), n = 49; and AD, n = 20) had positron emission tomography (PET) with [18F]Fluorodeoxyglucose ([18F]FDG) and [18F]Florbetapir, and magnetic resonance imaging (MRI) with Diffusion Tensor Imaging (DTI). In the first part of the study, we identified areas of fractional anisotropy (FA) reduction in angular bundle and fornix in the AD group. Among these regions, we selected for subsequent analyses a voxel of interest (VOI) in the angular bundle bilaterally. Then, using a voxel-based interaction model we examined the association of FA in the angular bundle, amyloid-β deposition, and also the potential interaction of these variables with [18F]FDG cerebral hypometabolism. In the AD group, [18F]FDG hypometabolism in the striatum, basal and mesial temporal, orbitofrontal, precuneus, anterior and posterior cingulate cortices was associated with the interaction between increase in [18F]Florbetapir standardized uptake value ratio (SUVR) in regions of interest and reduction in angular bundle FA. No significant clusters were identified in CN and MCI subjects. The interaction model, including amyloid-β deposition and WM disconnection, supports the concept of an integrative framework of AD pathophysiology where the combination of distinct pathological processes leads to progressive brain dysfunction in important cognitive-related areas